2021
DOI: 10.1042/cs20210821
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activation of AMP-activated protein kinase leads to early-onset polycystic kidney phenotype

Abstract: AMP-activated protein kinase (AMPK) plays a key role in the cellular response to low energy stress and has emerged as an attractive therapeutic target for tackling metabolic diseases. Whilst significant progress has been made regarding the physiological role of AMPK, its function in the kidney remains only partially understood. We use a mouse model expressing a constitutively active mutant of AMPK to investigate the effect of AMPK activation on kidney function in vivo. Kidney morphology and changes in gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
(105 reference statements)
1
4
0
Order By: Relevance
“…In previous studies using this model, we did not observe any overt phenotype in control mice with global or tissue-specific expression of WT γ1 because these mice showed no change in AMPK expression or activity relative to non-transgenic mice. 11 , 12 , 14 Consistent with our previous studies, we found no differences in PCa disease progression between Pten −/− and Pten −/− ; Ampk WT mice ( Figure S1A ), and we therefore combined Pten −/− and Pten −/− ; Ampk WT mice to generate a single control group, referred to as Pten −/− mice. We also confirmed that expression of the γ1 transgene had no obvious effect on the levels of endogenous α and β subunit proteins and that the transgene was expressed in anterior and dorsolateral ventral prostate lobes ( Figure S1B ).…”
Section: Resultssupporting
confidence: 86%
“…In previous studies using this model, we did not observe any overt phenotype in control mice with global or tissue-specific expression of WT γ1 because these mice showed no change in AMPK expression or activity relative to non-transgenic mice. 11 , 12 , 14 Consistent with our previous studies, we found no differences in PCa disease progression between Pten −/− and Pten −/− ; Ampk WT mice ( Figure S1A ), and we therefore combined Pten −/− and Pten −/− ; Ampk WT mice to generate a single control group, referred to as Pten −/− mice. We also confirmed that expression of the γ1 transgene had no obvious effect on the levels of endogenous α and β subunit proteins and that the transgene was expressed in anterior and dorsolateral ventral prostate lobes ( Figure S1B ).…”
Section: Resultssupporting
confidence: 86%
“…The targeting of a central regulator like AMPK as a treatment strategy comes with its own risks and challenges. In some studies, the chronic activation of AMPK has shown undesirable side effects such as cardiac and kidney hypertrophy and Alzheimer’s disease (Wilson et al 2021; Zimmermann et al 2020). However, clinical trials and animal studies with other AMPK agonists did not reveal harmful side effects, indicating that activating this central regulator is feasible and safe with the right compounds (López-Pérez et al 2021; Pinkosky et al 2016; Ray et al 2024; Cusi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MET (41 mg/ kg) is able to activate AMPK and slow cyst growth in a miniature pig model of ADPKD (Lian et al, 2019). Interestingly, in a mouse model expressing a constitutively active mutant of AMPK, there was early onset polycystic kidney phenotype and increased cAMP levels and ERK activation (Wilson et al, 2021). Thus, the maximal activation of p-AMPK in PKD kidneys may be insufficient to suppress mTORC1 and may even cause cystogenesis in mouse and rat models of PKD (Wilson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a mouse model expressing a constitutively active mutant of AMPK, there was early onset polycystic kidney phenotype and increased cAMP levels and ERK activation (Wilson et al, 2021). Thus, the maximal activation of p-AMPK in PKD kidneys may be insufficient to suppress mTORC1 and may even cause cystogenesis in mouse and rat models of PKD (Wilson et al, 2021). To inform further studies of MET in rodents and humans, elucidating the pattern of AMPK activation in the PKD kidney would be important.…”
Section: Discussionmentioning
confidence: 99%